Human gut microbes are susceptible to antimicrobial food additives in vitro - Hrncirova, Lucia; Hudcovic, Tomas; Sukova, Eliska; Machova, Vladimira; Trckova, Eva; Krejsek, Jan; Hrncir, Tomas (Folia microbiologica, 2019)
The aim of this work was to test the hypothesis that antimicrobial food additives may alter the composition of human gut microbiota by selectively suppressing the growth of susceptible gut microbes. To explore the influence of antimicrobial food additives on the composition of the human gut microbiota, we examined the susceptibility of both aerobic and anaerobic gut bacteria to sodium benzoate, sodium nitrite, and potassium sorbate, and their combinations, using a broth microdilution method. The tested bacteria exhibited a wide range of susceptibilities to food additives. For example, the most susceptible strain, Bacteroides coprocola, was almost 580 times more susceptible to sodium nitrite than the most resistant strain, Enterococcus faecalis. However, most importantly, we found that gut microbes with known anti-inflammatory properties, such as Clostridium tyrobutyricum or Lactobacillus paracasei, were significantly more susceptible to additives than microbes with known proinflammatory or colitogenic properties, such as Bacteroides thetaiotaomicron or Enterococcus faecalis. Our data show that some human gut microbes are highly susceptible to antimicrobial food additives. We speculate that permanent exposure of human gut microbiota to even low levels of additives may modify the composition and function of gut microbiota and thus influence the host's immune system. Whether the effect of additive-modified gut microbiota on the human immune system could explain, at least in part, the increasing incidence of allergies and autoimmune diseases remains to be shown.
Keywords: gastrointestinální trakt; Gastrointestinal Tract; Autoimmune diseases; Mucosal immunology; Food Additives; Anti-Bacterial Agents; Humans; Chou-Talalay method; střevní mikroflóra; Gut microbiota; potravinářské přísady; Dysbiosis; Gastrointestinal Microbiome; Food additives; lidé; antibakteriální látky